2014
DOI: 10.5152/tftrd.2014.39206
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Breast Cancer at Early Postoperative Period: Relationship to Shoulder Pain, Handgrip Strength, Disability, and Emotional Status

Abstract: Objective: To assess quality of life (QOL) of patients operated for breast cancer at early periods and to investigate its relationship to pain, handgrip strength (HS), disability, and emotional status. Material and Methods: Ninety-three female patients, operated unilaterally for breast cancer, were included. QOL by Short Form-36 (SF-36), depression by Beck Depression Inventory (BDI), shoulder pain intensity (rest-movement) by visual analog scale (VAS), handgrip strength (HS) by handheld dynamometer, and disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The five articles included in this review (Brandini et al, 2019;Buyukakincak et al, 2014;Esteban-Simón et al, 2021;Kaya et al, 2010;Koca et al, 2020) have a cross-sectional design and involved a total of 587 women BC survivors who were mostly recruited from Turkey (Buyukakincak et al, 2014;Kaya et al, 2010;Koca et al, 2020) with a mean age >50 years. The characteristics of the studies are summarized in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The five articles included in this review (Brandini et al, 2019;Buyukakincak et al, 2014;Esteban-Simón et al, 2021;Kaya et al, 2010;Koca et al, 2020) have a cross-sectional design and involved a total of 587 women BC survivors who were mostly recruited from Turkey (Buyukakincak et al, 2014;Kaya et al, 2010;Koca et al, 2020) with a mean age >50 years. The characteristics of the studies are summarized in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Of the studies included, only the study by (Buyukakincak et al, 2014) evaluated patients in the immediate postoperative period of mastectomy for BC. The other studies included patients who were in adjuvant treatment or had concluded systemic treatments for cancer.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast conserving surgeries involving the axillary region, and partial or total mastectomy surgeries are of great importance in the treatment of the breast cancer (3,4). However, as a result of these methods some complications such as pain, upper limb dysfunction, decreased range of motion, lymphedema and loss of muscle strength in upper limb can arise following treatment (5,6,7).…”
Section: Meme Kanseri Sonrası Lenfödem Gelişen Ve Gelişmeyen Kadınlarda üSt Ekstremite Fonksiyonu Postür Ve Yaşam Kalitesi Arasındaki İlmentioning
confidence: 99%
“…Breast cancer-related lymphedema is one of the most stressful symptoms and one of the most common complications for individuals due to its prognosis (Sakorafas et al 2006). Although improvements in treatment increase survival in breast cancer, shoulder dysfunction associated with upper extremity functions, upper extremity muscle weakness, and lymphedema are observed in patients after treatment (Lee et al, 2001, Radina et al 2004Gary, 2007;Büyükakıncak et al 2014). Voogd et al reported that women with lymphedema most frequently experience problems with the upper extremity (Voogd et al 2003).…”
Section: Introductionmentioning
confidence: 99%